Low-coverage whole genome sequencing of eleven species/subspecies in Dioscorea sect. Stenophora (Dioscoreaceae): comparative plastome analyses, molecular markers development and phylogenetic inference - Hu, Ke; Sun, Xiao-Qin; Chen, Min; Lu, Rui-Sen (Frontiers in Plant Science, 2023)
Dioscorea sect. Stenophora (Dioscoreaceae) comprises about 30 species that are distributed in the temperate and subtropical regions of the Northern Hemisphere. Despite being evolutionarily “primitive” and medically valuable, studies related to species identification and molecular phylogenetics in this section are still scarce. Here, we reported whole plastome sequences of 11 Stenophora species/subspecies, and performed comparative and phylogenetic analyses of them. The plastomes of Stenophora species ranged from 153,691 bp (D. zingiberensis) to 154,149 bp (D. biformifolia) in length, and they all contained the same 114 unique genes (i.e., 80 protein-coding genes, 30 transfer RNA genes, and four ribosomal RNA genes). Stenophora plastomes were highly conserved in gene structure, gene order and GC content, although variations at the IR/SC borders contributed to the whole length differences among them. The number of simple sequence repeats (SSRs) among the Stenophora species/subspecies varied from 74 (D. futschauensis) to 93 (D. zingiberensis), with A/T found to be the most frequent SSR. Seven highly variable regions (ndhD-ccsA, petA-psbJ, trnL-rpl32, psbZ-trnG, trnD-trnY, rpl32-ndhF, and rps16 intron) were identified with nucleotide diversity greater than 1.00%, which may be the best choices for future taxonomical, phylogenetic and population genetic studies. Phylogenomic analyses of these Stenophora species strongly supported D. biformifolia and D. banzhuana constituted the successive sister species to the other sampled species, which could be further divided into three clades. Overall, this study provided a new perspective for plastome evolution of Stenophora, and proved the role of plastome phylogenomic in improving the phylogenetic resolution. In addition, these results also provided an important reference for the protection and utilization of this economically important section.